Amniotic fluid index as indicator for pregnancy outcome in late third trimester - Majumdar, Anamika; Mallick, Kallol; Majumdar, Ritwika; Patel, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Amniotic fluid index is one of the major predictors of pregnancy outcome. Less AFI indicate growth restriction and renal anomalies of fetus, whereas more may indicate fetal GI anomalies, maternal diabetes mellitus, and so forth. Objectives were to establish reference standards for AFI for local population after 34 weeks of pregnancy and to decide an optimal scan interval for AFI estimation in third trimester in low-risk antenatal women. Methods: A prospective estimation of AFI was done in 83 healthy low risk pregnant women from 34 to 40 weeks at weekly intervals. The trend of amniotic fluid volume was studied with advancing gestational age. Statistical analysis was done using SPSS software (Version 16, Chicago, IL). Percentile curves (5th, 50th, and 95th centiles) were constructed for comparison with other studies. Cohen’s d coefficient was used to examine the magnitude of change at different time intervals. Results: Starting from 34 weeks till 40 weeks, 83 ultrasound measurements were available. The mean (standard deviation) of AFI values (in cms) were 34W:14.59(1.79), 35W: 14.25 (1.57), 36W: 13.17 (1.56), 37W: 12.48 (1.52), 38W: 12.2 (1.7), and 39W: 11.37 (1.71). The5th percentile cut-off was 8.7 cm at 40 weeks. There was a gradual decline of AFI values as the gestational age approached term. Significant drop in AFI was noted at two-week intervals. Conclusions: Appreciable changes occurred in AFI values as gestation advanced by two weeks. Hence, it is recommended to follow up low risk antenatal women every two weeks after 34 weeks of pregnancy.